Why is Instagram so Popular in Indonesia? Global Communication Features on Online Interaction - Aryati Hamzah; Siti Afrianty H Kundji; Rahayu Agustina Ishak; Nursapitri Djarati; Arfan Nagaring (Universitas Bina Mandiri Gorontalo, 2025)
Instagram is an application that allows users to share photos and videos. Instagram also offers features that allow users to interact with other people online. It is one of the most popular social media apps in the world and has been increasing in popularity in recent years. Instagram features include: Photo and Video Sharing: Users can share photo and video content with other users. Interact with Other Users: Users can follow other accounts, leave comments, and